Shear behavior of stainless-steel plate connectors for insulated precast concrete sandwich panels. (October 2022) - Lou, Xiaohang; Xue, Weichen; Bai, Haoyang; Li, Ya; Huang, Qian
Abstract: In this study, 24 double-shear tests were performed on precast concrete insulated sandwich panels using stainless-steel plate connectors. Parameters in the test program included connector shear directions (in-plane/out-of-plane), presence of insulation (with/without), cavity widths (30 mm/80 mm/120 mm) and connector heights (120 mm/160 mm). In order to test the pure shear capacity of connectors, the insulation was removed in the in-plane shear tests. The test results indicated that the connectors with 80 mm and 120 mm cavity width failed by shear buckling and the connectors with a cavity width of 30 mm were pulled out after buckling when subjected to in-plane shear. For the out-of-plane shear tests, bending of connectors occurred in the specimens without insulation, and connectors were pulled out in the specimens with insulation. For in-plane shear connectors with cavity widths of 30 mm, 80 mm and 120 mm, the shear capacities of 120 mm high connectors were 31.8 kN, 25.8 kN and 11.5 kN respectively, while the shear capacities of connectors with a height of 160 mm were 49.3 kN, 30.2 kN and 17.6 kN. The shear capacities of the out-of-plane connectors was only 3.7% of the in-plane connectors. It was also indicated that the presence of insulation significantly contributed to shear transfer in out-of-plane shear tests, leading to 28.6 times higher shear capacity than the specimens without insulation. Based on Basler's tension field theory, an analytical model was developed to predict the shear capacity of plate connectors. Compared with test results in this paper and other studies, the predictions were in good agreement.